A cosmopolitan calcifying benthic foraminifera in agglutinated disguise as a geochemical recorder of coastal environments - Tamara Sosnitsky; Vasilisa Krekova; Bar Elisha; Aleksey Sadekov; Adi Torfstein; Maria Holzmann; Hua Li; Sigal Abramovich; Sarit Ashckenazi-Polivoda (Proceedings of the National Academy of Sciences, 2025)
Calcifying foraminifera from the orders Rotaliida and Miliolida are widely used as geochemical proxies for recording paleoceanographic conditions, while agglutinated foraminifera are often overlooked since their tests are mostly composed of foreign particles. This study investigated the geochemical properties of Textularia agglutinans, a cosmopolitan agglutinated benthic species from the order Textulariida which has an exceptional inner calcareous test and is evolutionarily basal to Rotaliida. This study confirms the evolutionary link between textulariids and rotaliids based on their geochemistry and establishes T. agglutinans as a geochemical recorder of marine environments. Specimens from the Mediterranean coast of Israel were analyzed using laser ablation ICP-MS and compared to whole-test ICP-MS measurements of rotaliid and miliolid taxa from the same location. An Mg/Ca temperature calibration was established by LA-ICP-MS analyses of cultured specimens at 15, 17, 20, and 25 °C. Results show that T. agglutinans is a mid-Mg species (~19 to ~60 mmol/mol), with an Mg/Ca temperature correlation similar to high-Mg species. Its Pb, Zn, and Mn/Ca ratios are variable, generally overlapping with rotaliids and significantly lower than miliolids. Notably, T. agglutinans exhibits significantly higher Sr/Ca ratios (3.2 to 4.7 mmol/mol) compared to most foraminifera. Raman analyses reveal that the inner wall comprises a mix of aragonite and calcite, explaining these elevated Sr/Ca ratios. Rotaliida are the most prolific group of calcifying foraminifera. Our findings suggest that rotaliid tests evolved from an agglutinated textulariid ancestor with an inner aragonitic wall, a hypothesis that is further supported by the close phylogenetic relationship of the two groups.